Estudo da qualidade das águas adicionadas de sais produzidas no Estado do Ceará - Costa, Maria Tereza Pinto da (2013)
To the Resolution from the Board of Directions – RDC No 274/05, from the National Agency of Sanitary Vigilance (ANVISA), that approves the “Technical Regulation for Bottled Water and Ice”, the salt-added water is a bottled water that is prepared and bottled containing one or more salts, without any addition of sugars, sweeteners, flavors or other ingredients, destined for human consumption. This resolution does not specify the characteristics for identity fixing or the quality of the bottled salt-added water, and has as only requirement that the water used for its prepare is in accord with the microbiological, chemical and radioactive parameters of the “Quality of the Water for Human Consumption Norm”. However, the current Directive No. 2.914/11 from the Ministry of Health does not apply to the salt-added water after its bottling, nor to the water used as raw material for the product. Willing to evaluate the quality of the salt-added water in its two stages of manufacture, (well water, used as raw material and the bottled water, in 20-liter carboys) from salt-added water producer industries from the State of Ceará, samples were collected in 15 companies, in three distinct periods of time, totalling 270 samples. The microbiological analysis performed were: Determination of Total coliforms and Escherichia coli (Chromogenic substrate technique); Enterococcus, Pseudomonas aeruginosa, Clostridium perfringens (Filtering membrane technique); Heterotrophic bacteria (Culture in Depth technique), and phisico-chemical analysis; Determination of Nitrate, Nitrite (Spectrophotometric method); Residual Chlorine and pH (Electroanalytical measuringIt was verified that the well water used as raw material in 11 (73, 33%) of the 15 companies does not fill the standards of the water potability for human consumption. Regarding the bottled water, it was verified that in 14(93, 33%) of the companies, it does not follow the phisico-chemical and microbiological parameters for mineral water and for water for human consumption. It was concluded that an update in the sanitary legislation of the salt-added water product is necessary and urgent in order to prevent damages on the Health of the consumer population.